2018
DOI: 10.1002/hed.25437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serpinE1 overexpression on the primary tumor and lymph node, and lung metastases in head and neck squamous cell carcinoma

Abstract: Background Serpin Family E Member 1 (SerpinE1) overexpression associates with poor clinical outcome in head and neck squamous cell carcinoma (HNSCC) patients. This study analyzed the role of serpinE1 in HNSCC dissemination. Methods We studied the phenotypic characteristics and dissemination of HNSCC cells overexpressing serpinE1 using an orthotopic model and the association between serpinE1 overexpression and clinicopathological variables in patients included in The Cancer Genome Atlas database. Results Serpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…The plasminogen activator inhibitor-1 (PAI-1) encoded by SERPINE1 was an important regulator of the uPA system, which was supposed to inhibit the activation of uPA, but paradoxical studies revealed that SERPINE1 might play a role in promoting the carcinogenesis of many cancers [23]. Many investigations have implied that SERPINE1 is overexpressed in various cancers, including GC [24], head and neck cancer [25] and colorectal cancer [26], and this overexpression correlated with the aggressiveness and invasiveness of tumor cells. Additionally, the downregulation of SERPINE1 suggested a suppressive effect on the phenotype of glioma tumor cells by activating the p53 signaling pathway and suppressing the adverse invasion and metastasis of nasopharyngeal carcinoma cells in vitro [27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The plasminogen activator inhibitor-1 (PAI-1) encoded by SERPINE1 was an important regulator of the uPA system, which was supposed to inhibit the activation of uPA, but paradoxical studies revealed that SERPINE1 might play a role in promoting the carcinogenesis of many cancers [23]. Many investigations have implied that SERPINE1 is overexpressed in various cancers, including GC [24], head and neck cancer [25] and colorectal cancer [26], and this overexpression correlated with the aggressiveness and invasiveness of tumor cells. Additionally, the downregulation of SERPINE1 suggested a suppressive effect on the phenotype of glioma tumor cells by activating the p53 signaling pathway and suppressing the adverse invasion and metastasis of nasopharyngeal carcinoma cells in vitro [27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that upregulated THBS1 was associated with poor prognosis in gastric cancer. SERPINE1 functions as the principal inhibitor of tPA and uPA, which promotes the metastasis of tumors [27,28]. Our study showed that upregulated SERPINE1 was associated with a poor prognosis in gastric cancer.…”
Section: Discussionmentioning
confidence: 75%
“…SERPINE1 is considered an oncogene in various types of cancers and can enable cancer cells to gain new properties such as migration, EMT, and apoptosis resistance ( 25 26 ).The expression of SERPINE1 was quantified in four HNSCC cell lines ( Figure 7A ). Then, in order to measure the potential effects of SERPINE1 on LSCC, we transfected SERPINE1 siRNAs to knockdown its expression in Fadu cells.…”
Section: Resultsmentioning
confidence: 99%